Does eWOM affect guests' experience expectation? An empirical analysis within the hotel and tourism sector / Nor Diyana Mohammed Shobri, Lennora Putit and Amirah Ahmad Suki - Mohammed Shobri, Nor Diyana; Putit, Lennora; Ahmad Suki, Amirah (Faculty of Business and Management, 2021)
Nowadays, progressive developments in information technology and latest communication techniques have brought about increasingly significant variations in consumer behaviour. These changes have created a focused shift in companies' business and marketing strategies. The hotel and tourism industry in particular, has been histrionically influenced by an electronic word-of-mouth (e-WOM) form of communication. This study aims to examine the extent to which e-WOM influences customer experience in a resort hotel setting. Using purposive sampling technique, a total of 135 usable online survey questionnaire feedbacks were collected from targeted respondents and subsequently used for data analyses. The data were analysed using SmartPLS software. Empirical results have revealed positive and significant relationships between e-WOM and all four dimensions of customer experience. The results emphasized the importance of e-WOM in the resort hotel industry and provided practical implications for the resort operators to enhance their guests' level of expected experience.